2020
DOI: 10.3389/fcell.2020.595969
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase 12 Protects Endplate Cartilage From Degeneration Regulated by IGF-1/PI3K/CREB Signaling Pathway

Abstract: Lumbar intervertebral disc degeneration (IVDD) is the most common cause of low back pain (LBP). Among all the factors leading to IVDD, lumbar cartilage endplate (LCE) degeneration is considered a key factor. In the present study, we investigate the effect and regulation of carbonic anhydrase 12 (CA12) in LCE, which catalyzes hydration of CO 2 and participates in a variety of biological processes, including acid–base balance and calcification. Our results show that CA12, downregulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…The results confirmed that transfection of CA XII siRNA could significantly reverse the increase of collagen II and aggrecan protein expression caused by HSYA in the NP cells, and weaken the inhibitory effect of HSYA on MMP-13 protein expression. The results were consistent with those from Chen et al ( 18 ) and Zhao et al ( 38 ). Therefore, we hypothesized that CA XII may be an important target for HSYA to exert the regulation of ECM homeostasis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results confirmed that transfection of CA XII siRNA could significantly reverse the increase of collagen II and aggrecan protein expression caused by HSYA in the NP cells, and weaken the inhibitory effect of HSYA on MMP-13 protein expression. The results were consistent with those from Chen et al ( 18 ) and Zhao et al ( 38 ). Therefore, we hypothesized that CA XII may be an important target for HSYA to exert the regulation of ECM homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, they also found that overexpression of CA XII could rescue IL-1β-stimulated endplate chondrocyte apoptosis, both in vitro and in vitro ( 18 ). Furthermore, CA XII could also protect inner plate cartilage from the degradation of ECM and collagen regulated by the IGF-1/PI3K/CREB signaling pathway ( 38 ). CA XII inhibition may not only disrupt the pH, which leads to lactate accumulation in NP cells, but also reduce the protein expression level of collagen II and aggrecan ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chothe reported that IGF1 upregulated the expressions of the sodium-dependent vitamin C transporter 2 (SVCT2), which facilitate cellular uptake of ascorbic acid from the ECM to maintain the collagen synthesis (Chothe et al, 2013). Zhao et al unveiled that the activation of the IGF1/PI3K/CREB/CA12 signaling pathway attenuated IVDD by maintaining anabolism and preventing disc cell apoptosis (Zhao et al, 2020). Furthermore, several studies have demonstrated that IGF signaling activation slows IVDD by increasing ECM synthesis, cell proliferation, and inhibiting inflammatory responses, ECM degradation, and cell apoptosis, which are primarily regulated by the PI3K/Akt and MEK/ERK pathways (Pratsinis and Kletsas, 2007;Mavrogonatou and Kletsas, 2010;Pratsinis et al, 2012;Wei et al, 2013;Liu et al, 2015;Tao et al, 2015;Xu et al, 2019;Tian et al, 2020).…”
Section: Igf Signalingmentioning
confidence: 99%
“…Several studies have shown that IGF1 can promote the synthesis of ECM (Osada et al, 1996;Gruber et al, 2004;Moon et al, 2008;Kim et al, 2010;Hayes and Ralphs, 2011;Huang et al, 2011b;Illien-Junger et al, 2012;Chothe et al, 2013;Liu et al, 2014;Tao et al, 2015;Chen et al, 2020;Zhao et al, 2020). It also prevents ECM degradation by inhibiting MMPs, which increases the amount of matrix in the intervertebral disc and delays the progression of IVDD.…”
Section: Igf Signaling Inhibits Ecm Degradation and Enhances Ecm Synthesismentioning
confidence: 99%
See 1 more Smart Citation